Creating Connections, Building Community: The Role of Oral History Collections in Documenting and Sharing Campus Diversity - Craft, Anna R. (Serials review, 2018)
The collection and sharing of oral history is a growing area that libraries and archives are using to connect with their communities and document campus diversity. This column discusses opportunities for libraries and archives to include diverse and underrepresented voices in the historical record, highlighting the Wolf Tales project from the North Carolina State University Libraries, which was the topic of a talk by Virginia Ferris at the 2018 North Carolina Serials Conference. This column discusses that presentation and briefly examines oral history projects at several other institutions, providing perspective on the efforts to use oral histories to document campus and community diversity in the profession. Further resources for institutions interested in pursuing or growing oral history programs are also provided.